2020
DOI: 10.1016/j.jrp.2019.103886
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in humor production ability: A meta-analysis

Abstract: We offer the first systematic quantitative meta-analysis on sex differences in humor production ability. We included studies where participants created humor output that was assessed for funniness by independent raters. Our meta-analysis includes 36 effect sizes from 28 studies published between 1976 and 2018 (N = 5057, 67% women). Twenty of the 36 effect sizes, accounting for 61% of the participants, were not previously published.Results based on random-effects model revealed that men's humor output was rated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 104 publications
6
34
0
1
Order By: Relevance
“…Both traits are pervasive in humor research, and both are associated with viewing oneself as a funny person (Silvia et al, 2020) and using humor in everyday life (Heintz, 2017). For gender, men's self-ratings were higher than women's, consistent with a large literature on lower humor self-efficacy in women (Caldwell & Wojtach, 2020;Hooper et al, 2016;Silvia et al, 2020) and an edge for men in lab-based humor tasks (Greengross et al, 2020). For both personality and gender, the effects were generally small in magnitude.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Both traits are pervasive in humor research, and both are associated with viewing oneself as a funny person (Silvia et al, 2020) and using humor in everyday life (Heintz, 2017). For gender, men's self-ratings were higher than women's, consistent with a large literature on lower humor self-efficacy in women (Caldwell & Wojtach, 2020;Hooper et al, 2016;Silvia et al, 2020) and an edge for men in lab-based humor tasks (Greengross et al, 2020). For both personality and gender, the effects were generally small in magnitude.…”
Section: Discussionsupporting
confidence: 54%
“…In American and UK samples, for example, women have lower humor self-efficacy (Caldwell & Wojtach, 2020;Silvia et al, 2020) and view being a funny person as more peripheral to their self-concept (Silvia et al, 2020). A meta-analysis of lab-based humor production studies found a small advantage for men (Greengross et al, 2020), so these self-beliefs have parallels in behavioral contexts.…”
Section: Self-rated Humormentioning
confidence: 99%
“…Should cultural norms sever these associations, then we may expect people to give humor less priority. However, there has yet to be a comprehensive examination of the cultural differences in the function of humor as a pathway to status (Greengross, Silvia, & Nusbaum, ) and so this idea warrants investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, for example, there are widely held stereotypes about gender and humor, such as the belief that "women aren't funny" (e.g., Hitchens, 2007;Hooper et al, 2016;Mickes et al, 2012). A recent meta-analysis did show a small advantage for men (Greengross et al, 2020), but the proposed…”
Section: Discussionmentioning
confidence: 99%